1974
DOI: 10.1002/zaac.19744050207
|View full text |Cite
|
Sign up to set email alerts
|

Gitterschwingungsspektren. IX. Pyritstruktur. FIR‐Spektren und Normalkoordinatenanalyse von MnS2, FeS2 und NiS2

Abstract: Die FIR‐Spektren von MnS2, FeS2 und NiS2 werden im Bereich von 600 bis 30 cm−1 analysiert und den fünf IR‐aktiven Translationsschwingungen des Pyritgitters zugeordnet. Die Symmetriekoordinaten der Gitterschwingungen und angenäherte Schwingungsformen konnten aus der Faktorgruppe abgeleitet werden. Die große bathochrome Verschiebung (bis 220 cm−1) der Absorptionsmaxima des MnS2 gegenüber FeS2 wird im Zusammenhang mit der Stärke der Metall–Schwefel‐Bindung diskutiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

1974
1974
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 6 publications
0
10
0
2
Order By: Relevance
“…The number and symmetries of the Raman and infrared-active modes of pyrite have been determined using group theoretical methods. 49 The irreducible representations of the vibrations of pyrite are:…”
Section: B Vibrational Contribution To the Energy Of Iron Disulfide mentioning
confidence: 99%
“…The number and symmetries of the Raman and infrared-active modes of pyrite have been determined using group theoretical methods. 49 The irreducible representations of the vibrations of pyrite are:…”
Section: B Vibrational Contribution To the Energy Of Iron Disulfide mentioning
confidence: 99%
“…Thus, from far-infrared spectroscopic studies it was shown that the lattice dynamics of the isoelectronic OsS2 and PtP2 are very similar (Lutz et al 1976(Lutz et al , 1985 notwithstanding the different anionic units ($2 and P2) involved. In order to establish the Raman frequencies of pyrite-type compounds, especially with regard to the lattice dynamics of OsS2 and PtPz (the internal $2 and P2 stretching modes are only Raman allowed), we recorded single crystal Raman spectra of RuS2,RuSe2,OsS2,PtP2,and PtAs> Group theory treatment of the pyrite structure belonging to the space group Pa3-T 6 (Lutz and Willich 1974) yields five Raman-allowed zone centre phonon modes (unit cell (factor) group Th), viz., F=Ag+Eg+ 3Fg. The symmetry coordinates of the lattice vibrations are given elsewhere (Lutz and Willich 1974).…”
Section: Introductionmentioning
confidence: 99%
“…In order to establish the Raman frequencies of pyrite-type compounds, especially with regard to the lattice dynamics of OsS2 and PtPz (the internal $2 and P2 stretching modes are only Raman allowed), we recorded single crystal Raman spectra of RuS2,RuSe2,OsS2,PtP2,and PtAs> Group theory treatment of the pyrite structure belonging to the space group Pa3-T 6 (Lutz and Willich 1974) yields five Raman-allowed zone centre phonon modes (unit cell (factor) group Th), viz., F=Ag+Eg+ 3Fg. The symmetry coordinates of the lattice vibrations are given elsewhere (Lutz and Willich 1974). Until very recently, only incomplete Raman data of RuS2 and RuSe2 were available in the literature (Taguchi et al * This is contribution LXI of a series of papers on lattice vibration spectra 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Da ein entsprechendes Verhalten bei den IR-und Raman-Spektren, z. B. beim Vergleich von MnS2 und FeS2 , beobachtet wurde 3 ' 4 , beabsichtigten wir durch eine Kraftkonstantenrechnung zum Verständnis der Bindungseigenschaften von Pyriten beizutragen. Ferner sollten mit Hilfe einer numerischen Normalkoordinatenrechnung die von uns aufgrund geometrischer Über-legungen vorgeschlagenen Schwingungsformen des Pyritgitters 3 überprüft werden.…”
unclassified
“…Alle fünf optischen Phononen (k = 0) der Rasse Fu des Pyritgitters (Faktorgruppenanalyse [3][4][5][6] ) konnten bisher in den FIR-Spektren folgender Pyrite registriert werden 3 ' 7 : MnS2, FeS2 , RuS2 , RuSe2, RuTe2, OsS2 und PtP2 . Die fünf erlaubten Raman-aktiven Schwingungen wurden bisher noch bei keiner Verbindung vollständig beobachtet 4 ' 8 ' 9 .…”
unclassified